2021
DOI: 10.1007/jhep12(2021)001
|View full text |Cite
|
Sign up to set email alerts
|

Scalar-tensor theories within Asymptotic Safety

Abstract: Asymptotic Safety provides an elegant mechanism for obtaining a consistent high-energy completion of gravity and gravity-matter systems. Following the initial idea by Steven Weinberg, the construction builds on an interacting fixed point of the theories renormalization group (RG) flow. In this work we use the Wetterich equation for the effective average action to investigate the RG flow of gravity supplemented by a real scalar field. We give a non-perturbative proof that the subspace of interactions respecting… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 212 publications
(263 reference statements)
2
30
0
Order By: Relevance
“…The generated matter interactions are symmetric under the global symmetries of the kinetic terms. This observation has been explained based on the diagrammatic structure of the flow equation in [26], and has been shown more formally for shift-symmetry in scalar-gravity models in [58]. In [1] it has additionally been shown that the full global symmetry of the kinetic term for scalars is not broken to a discrete symmetry by gravity fluctuations.…”
Section: -Unavoidable Interactionsmentioning
confidence: 89%
See 2 more Smart Citations
“…The generated matter interactions are symmetric under the global symmetries of the kinetic terms. This observation has been explained based on the diagrammatic structure of the flow equation in [26], and has been shown more formally for shift-symmetry in scalar-gravity models in [58]. In [1] it has additionally been shown that the full global symmetry of the kinetic term for scalars is not broken to a discrete symmetry by gravity fluctuations.…”
Section: -Unavoidable Interactionsmentioning
confidence: 89%
“…When gravity is interacting, one expects that it will mediate effective matter interactions -simply because gravity fluctuations cannot be decoupled from matter. Indeed, certain matter self-interactions and non-minimal matter-gravity couplings are unavoidable at an asymptotically safe fixed point [27,23,32,11,29,39,38,16,58,35]. These interactions are determined by the global symmetries of the kinetic terms of the matter fields.…”
Section: -Unavoidable Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The setting with linear split and Landau gauge α gf → 0 is commonly used when exploring the interplay between gravity and matter couplings within the framework of asymptotically safe quantum gravity [18,21,27,[45][46][47][48][49][50][51][52][53][54][55][56][57], alternative gauge choices and parameterizations are explored in [17,22,[58][59][60]. The impact of matter on the flow of gravitational couplings was investigated in [19,[61][62][63][64][65][66][67][68][69][70][71][72][73][74][75]. ii) "Unimodular gravity": In this setting, the conformal mode is non-dynamical, and the symmetry group (before breaking by the regulator) is the group of transverse diffeomorphisms [76][77][78][79][80][81][82][83].…”
Section: Setup For the Evaluation Of Beta Functionsmentioning
confidence: 99%
“…5 Weak-gravity bound in the vanishing regulator limit Gravity-matter interactions can induce higher-order self-interactions in the matter sector [17,45,46,58,75]. Consequently, there is no fixed point that is fully non-interacting in the matter sector, but interacting in the gravitational sector.…”
Section: Interpretation and Outlookmentioning
confidence: 99%